An annotated checklist of house dust mites (Acari: Acariformes) of Türkiye - Medeni Aykut (Persian Journal of Acarology)
This checklist of house dust mites (Acari: Trombidiformes, Sarcoptiformes) from Türkiye is based on published data and private collections. The species are listed alphabetically. In total, 33 dust mite species and their zoogeographical distributions are presented. This study represents the first checklist of house dust mite fauna in Türkiye.